1995
DOI: 10.1128/iai.63.7.2443-2449.1995
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enteritidis colonization of the reproductive tract and forming and freshly laid eggs of chickens

Abstract: Salmonella enteritidis colonizes the tissues of the chicken ovary and oviduct, presumably contaminating eggs and thereby contributing to human outbreaks of salmonellosis. In this study, commercial adult laying hens were given an oral inoculation of 10 8 S. enteritidis organisms. Tissues from various organs, the intestines, and the reproductive tract, including freshly laid eggs, were collected daily for up to 40 days postinoculation (p.i.). Within 2 days p.i. S. enteritidis was detected by culture in pools of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
1
12

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(109 citation statements)
references
References 22 publications
(37 reference statements)
7
89
1
12
Order By: Relevance
“…It is now widely accepted that the primary route of egg contamination is via deposition of SE from the infected RT directly into the internal contents of eggs prior to oviposition (Arnold et al, 2014;Gast and Holt, 2000;Keller et al, 1995;Shivaprasad et al, 1990). It is also known that the hen egg presents a hostile environment for efficient propagation of SE.…”
Section: Colonization and Survival In The Internal Contents Of Eggsmentioning
confidence: 99%
“…It is now widely accepted that the primary route of egg contamination is via deposition of SE from the infected RT directly into the internal contents of eggs prior to oviposition (Arnold et al, 2014;Gast and Holt, 2000;Keller et al, 1995;Shivaprasad et al, 1990). It is also known that the hen egg presents a hostile environment for efficient propagation of SE.…”
Section: Colonization and Survival In The Internal Contents Of Eggsmentioning
confidence: 99%
“…Other serovars (such as S. Enteritidis and S. Typhimurium) are more effective at spreading from the gastrointestinal tract to other organs, causing a systemic infection (Humphrey et al, 1989a;Keller et al, 1995;Okamura et al, 2001a;Okamura et al, 2010;Shivaprasad et al, 2013). In recent studies performing comparative genome analysis, it was concluded that S. Gallinarum and S. Enteritidis are highly related and that S. Gallinarum may be a direct descendant of S. Enteritidis, which has lost part of its genome and became host adapted.…”
Section: Factors Influencing Salmonella Pathogenesis In Chickensmentioning
confidence: 99%
“…Yolk contamination points to the ovary as the site of origin of the egg contamination . A systemic spread of Salmonella infection in the hen can lead to the colonization of the ovary (Keller et al, 1995) and Salmonella (in particular S. Enteritidis) is strongly believed to interact with the cellular components of the preovulatory follicles, which lead to the production of the egg yolk. Ovary contamination with Salmonella can result in colonization of the preovulatory follicles, but not necessarily in the production of yolk-contaminated eggs.…”
Section: Primary Contaminationmentioning
confidence: 99%
See 2 more Smart Citations